Dietary Inflammatory Index (DII®) and Lung Function in Adults from Ten European Countries – Evidence from the GA2LEN Follow-Up Survey. (29th May 2020) - Mendes, Francisca de Castro; Thawer, Sumaiyya; Shivappa, Nitin; Hebert, James R; Burney, Peter G J; Garcia-Larsen, Vanessa
Abstract: Objectives: To investigate the association between Dietary Inflammatory Index (DII ® ) and lung function in European adults. Methods: The study sample was drawn from the Global Allergy and Asthma Network of Excellence (GA 2 LEN) screening survey, in which 55, 000 adults aged 15 to 75 years answered a postal questionnaire on respiratory symptoms. A stratified random sample was obtained for follow-up. A cross-sectional study was conducted in this sample ( n = 3241), which included ascertainment of dietary intake and measures of lung function. Participants completed the internationally validated GA 2 LEN food frequency questionnaire (FFQ), which enquired about usual intake of 245 food items. The dietary inflammatory index (DII®) was derived to ascertain the inflammatory potential of the diet (minimum and maximum reference range −8.87 to 7.98; i.e., the higher the score the more pro-inflammatory the diet). Participants performed post-bronchodilator spirometry, from which forced vital capacity (FVC), the ratio between the forced exhaled volume in 1 second (FEV1) and FVC (FEV1/FVC), FVC below lower limit of normal (FVC < LLN; (restriction)) and FEV1/FVC < LLN (airway obstruction) were calculated. Exposures and lung function outcomes were weighted to obtain estimated population parameters. Potential confounders included age, sex, height, body mass index, smoking status, country, education and employment. Adjusted regressions were used to investigate the associations between DII and respiratory outcomes. Results: The mean age of participants was 48 years (SD ± 15.1), and the median DII was −1.53 (IQR difference 3.5). In the fully adjusted models, a one-unit increase in DII score was statistically significantly associated with a lower FEV1 /FVC (β-coefficient −0.46, 95% CI −0.80, −0.12; P -value = 0.008) and with airway obstruction (odds ratio [OR] 1.17, 95% CI 1.03, 1.34; P -value = 0.018]. There was no association with the other lung function outcomes. Conclusions: A more pro-inflammatory diet was associated with greater airway obstruction amongst European adults. Funding Sources: FCM is funded by The Fulbright Commission and by the Fundação para a Ciência e Tecnologia (SFRH/BD/144, 563/2019). This work was conducted as part of The GA 2 LEN Working Group WP1.2 Epi & Clinical Studies. GA 2 LEN was funded by the EU Framework Programme for Research, contract No FOOD-CT-2004–506, 378.